2013
DOI: 10.1007/978-3-642-33194-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Transition Regions: Green Innovation and Economic Development

Abstract: This paper has three main aims. The first of these is to discuss and critique the main spatial and non-spatial theories that address methods by which societies may transition from a hydrocarbon to a post-hydrocarbon technological regime. It is argued that the first approach, which combines urban regime theory of politics with ecological modernization theory, is ultimately contradictory and rooted in an inadequate sustainability discourse. The second approach is more interesting, not least because it adopts an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The results of our study partly reinforce the findings of prior work (Cooke, 2013;Rösler et al, 2013;Schönberger, 2013;Watanabe, 1999). When pursuing a transition towards a RES, policymakers play an essential role by routing R&D efforts and creating an adequate environment that motivates investments and interaction between public and private sectors (Foxon et al, 2005;Jacobsson and Bergek, 2004;Späth and Rohracher, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study partly reinforce the findings of prior work (Cooke, 2013;Rösler et al, 2013;Schönberger, 2013;Watanabe, 1999). When pursuing a transition towards a RES, policymakers play an essential role by routing R&D efforts and creating an adequate environment that motivates investments and interaction between public and private sectors (Foxon et al, 2005;Jacobsson and Bergek, 2004;Späth and Rohracher, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our results demonstrate quantitatively that it is crucial for municipalities to focus first on strengthen local knowledge about RES [KNOW] to improve their performance in RES development (Hypothesis H3). Prior qualitative research already suggested this argument (Cooke, 2013;Jacobsson and Bergek, 2004;Smit et al, 2007;Späth and Rohracher, 2012). Municipalities can generate this specific knowledge by developing policy instruments with focus on renewable energy R&D (Hildén, 2011;Paraskevopoulou, 2012), R&D subsidies (Cantner et al, 2016;Noailly and Smeets, 2015), scientific education in public research institutes and universities (Mowery et al, 2010;Paraskevopoulou, 2012) or municipally-owned companies for the development of renewable energy projects (Gustafsson et al, 2015;Howells, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A number of scholars have argued that innovation research including the MLP is enhanced through dialogue with geography and vice versa (Bulkeley et al, 2010;Cooke, 2009;Coenen et al, 2011;Marvin, 2009, 2010;Truffer, 2008). For example, Truffer and Coenen (2011, page 18) This leads to a call for 'geographies of (sustainable) transition', which, we believe, can be generated using resource peripheries research.…”
Section: Resource Peripheriesmentioning
confidence: 99%
“…Geographers at large have already made constructive comments, contributions and critiques on transition studies (e.g. Cooke, 2009;Hodson and Marvin, 2009;Shove and Walker, 2007;Truffer, 2008) but to date none of these have specifically juxtaposed insights on the geography of innovation with that of socio-technical transitions (with some very recent exceptions like Lawhon and Murphy, press;Coenen and Truffer, 2012). At the same time we should acknowledge that environmental economic geography, i.e.…”
mentioning
confidence: 99%